Performance of influenza rapid antigen testing in influenza in emergency department patients. Issue 1 (22nd December 2009) - Biggs, C; Walsh, P; Overmyer, C L; Gonzalez, D; Feola, M; Mordechai, E; Adelson, M E; Iacono, K T
Abstract : Background: The use of rapid antigen tests to triage specimens for polymerase chain reaction (PCR) testing from emergency department patients with influenza-like illness during surveillance for novel influenza viruses has been suggested. Objective: To measure the observed sensitivity and specificity for a widely used rapid antigen test (Binax) using a PCR-based assay (Medical Diagnostic Laboratories). Methods: Nasopharyngeal samples were taken with flocked swabs (Copan Diagnostics) from patients presenting to the emergency department of a community hospital. Samples were analysed using a rapid antigen and a PCR-based test. PCR testing was used as the criterion reference. Sensitivity and specificity were calculated for influenza and influenza A. Positive predictive values were calculated over a range of possible prevalence. Results: Samples from 566 unique patients were tested using both methods. Sensitivity was 69.1% (95% CI 58.9% to 78.1%) and specificity was 97.7% (95% CI 95.8% to 98.8%) for the detection of any influenza and 75.3% (95% CI 64.7% to 84.0%) and 97.8% (95% CI 95.9% to 98.9%), respectively, for influenza A only. The resultant positive predictive value ranges from 23% to 77% when the prevalence ranges from 1% to 10%. Conclusion: When planning early outbreak surveillance, provision of adequate PCR testing capacity rather than triaging specimens using rapid antigen testing for influenza is advisable.